A Dictionary of Zoology - Edited by Allaby, Michael (Oxford Oxford University Press, 2014)
The most up-to-date and authoritative dictionary of zoology available. It contains over 6,000 A-Z entries covering all aspects of the subject, from behavioural ecology and conservation biology to cytology and taxonomy. This is an essential source of reference for students and teachers of zoology as well as naturalists.
Include Appendix
Keywords: Zoology